Strategi Penerapan Sistem Informasi Akuntansi Pada UMKM (Studi Kasus pada Usaha Permen Lolipop Qiyam di Madyopuro Malang) - Adhim, Fauzan; Amin, Moh.; Hasanah, Naimatul (Universitas Islam Malang, 2025)
This research aims to examine the challenges encountered and to develop strategies for implementing the Accounting Information System (AIS) in the micro, small, and medium enterprise (MSME) Permen Lolipop Qiyam, located in Madyopuro, Malang City. As a sector that plays a crucial role in supporting the national economy, MSMEs continue to face significant difficulties in adopting modern accounting system, particularly due to limited human resources, low accounting knowledge, and inadequate technological and digital infrastructure. The study applies a descriptive qualitative method with a case study approach, where data were obtained through interviews, observations, and documentation involving the owner, manager, and employees directly engaged in financial and operational activities. The results reveal that the financial recording at Permen Lolipop Qiyam is still conducted manually using simple bookkeeping, which leads to financial information that is neither accurate nor systematically organized. To overcome these issues, efforts should focus on enhancing the accounting literacy of business actors, implementing simple and practical financial recording formats, and providing gradual mentoring in the use of digital accounting tools. These measures are expected to improve efficiency, accuracy, and transparency in financial management and to encourage MSMEs to transition toward a sustainable, technology-based digital Accounting Information System.Keywords: Accounting information system, msme, financial recording, competency improvement, digital technology implementation.